Effective half-lives for 137Cs in dairy milk from alpine ecosystems and the controlling factors. (April 2023) - Meusburger, Tobias; Lettner, Herbert; Hubmer, Alexander; Hörger, Anja C.; Friedl, Gertrude; Tippelt, Gerold; Marbach, Matthias
Abstract: Alpine regions in the federal state of Salzburg (Austria) have been intensively contaminated by Chernobyl fallout, necessitating long-term monitoring programs. The sites predominately affected are those in areas with soil developed on silicate bedrock, as these soils tend to be acidic, favouring high transfer factors for 137 Cs. In addition, nutrient deficiency, low mineral and high organic matter content, and tough climatic conditions are causing the slow migration of 137 Cs in the soil, which are associated with long effective half-lives in the biosphere. As a quantitative measure for effective half-lives, milk has been collected at nine alpine seasonal stock farming sites since 1988; at four sites, the monitoring is still ongoing (2020). For the period between 1999 and 2020, the decrease of 137 Cs can be reasonably fitted with one effective half-life describing the time-trend. The effective half-lives obtained by this procedure vary between 9.3 ± 0.9 years and 18.8 ± 3.4 years. The effective half-lives show a weak negative correlation with the half-value depth of 137 Cs, defined as the depth of the upper soil layer containing half of the deposited fallout inventory. The majority of the inventory is bound in the rooting zone of 0–10 cm, which is reflected by the small half value depths in the range between 3.2 and 4.4 cm. The soils investigated are acidic with pH values between 3.78 and 4.88, showing a pronounced negative correlation with the effective half-lives of 137 Cs in milk. The data indicate that in these soils rich in organic matter, which are also almost totally devoid of clay minerals and have a very low clay size fraction, pH may be the dominating factor influencing the effective half-lives of 137 Cs plant uptake and the subsequent contamination of milk. Highlights: Depth distribution of 137 Cs in alpine soils. Effective half-life of 137 Cs contamination in milk from alpine production sites. Correlation of soil pH with effective half-life of 137 Cs in milk from alpine production sites. Dependence of effective half-life of 137 Cs in milk on soil parameters.